2019
DOI: 10.1371/journal.pone.0213982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition education on hemoglobin level in pregnant women: A quasi-experimental study

Abstract: BackgroundAnemia during pregnancy is a major public health problem globally with multiple causes including inadequate dietary intakes. The aim of the study was to assess the effect of nutrition education on nutritional knowledge, hemoglobin level and dietary intake of anemic pregnant women.Materials and methodsA quasi-experimental study was conducted among 115 mild to moderately anemic pregnant women attending ante natal clinics. Pregnant women were consecutively enrolled and assigned to receive nutrition educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
79
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 16 publications
6
79
0
5
Order By: Relevance
“…In the case of the mothers having with poor health and nutritional knowledge contribute to women being less sensitive to child and her nutritional status or less responsive to health and nutrition issues in terms of food choices and barriers such as food cost, accessibility, availability, lack of cooking skills [17,35]. As we found that DBM was more prevalent in mothers who had a lower level of education, therefore, providing nutrition education during pregnancy could bridge this nutritional knowledge gap in Nepal [36].…”
Section: Discussionmentioning
confidence: 69%
“…In the case of the mothers having with poor health and nutritional knowledge contribute to women being less sensitive to child and her nutritional status or less responsive to health and nutrition issues in terms of food choices and barriers such as food cost, accessibility, availability, lack of cooking skills [17,35]. As we found that DBM was more prevalent in mothers who had a lower level of education, therefore, providing nutrition education during pregnancy could bridge this nutritional knowledge gap in Nepal [36].…”
Section: Discussionmentioning
confidence: 69%
“…In the case of the mother having poor health and nutritional knowledge, it leads to women being less sensitive to child and her nutritional status in terms of food choices and barriers such as food cost, accessibility, availability, lack of cooking skills [19]. As we found that DBM was more prevalent in mothers who had a lower level of education, therefore, providing nutrition education during pregnancy could bridge this nutritional knowledge gap in Nepal [40].…”
Section: Discussionmentioning
confidence: 76%
“…Similar results were reported in a quasi-experimental study done in the Tribhuvan University Teaching Hospital in Kathmandu, Nepal, showing that nutrition education emphasizing iron-rich food consumption was positively associated with improved hemoglobin levels. 29 A randomized study among pregnant women in Ghana indicated a significant positive relationship between dietary practices and improvement of hemoglobin levels in pregnant women. 30 Similarly, in a pre-test post-test study done at Kaengkhoi Hospital, Saraburi, Thailand, health education focused on participants' knowledge of iron deficiency anemia and compliance of pregnant women regarding iron supplementation, and mean hematocrit levels of pregnant women were significantly improved after 3 months of the intervention program.…”
Section: Discussionmentioning
confidence: 99%